CORRELATION BETWEEN POLYMORPHONUKLEAR (PMN) LEUKOCYTE LEVELS AND GINGIVITIS IN THE UMS SECURITY UNIT - Karyadi, Edi; Anwaristi, Aprilia Yuanita; Runting, Nina; Widianti, Marinda (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2025)
Gingivitis is a periodontal disease that is often found in the oral cavity. According to Health Research in 2018, the prevalence of gingivitis in Indonesia is ranked second which shows a figure of 96.58%.  The causes of gingivitis are grouped into local factors and systemic factors. Local factors include caries, failed restorations, and piles of food waste, while systemic factors include nutritional, hormonal, and hematology. An abnormal hematological condition that can cause gingivitis is increased polymorphonuclear leukocyte levels in the blood circulation. Polymorphonuclear leukocyte levels can be affected by a person's sleep quality, poor sleep quality can trigger an increase in leukocyte levels. Poor sleep quality is vulnerable to being experienced by shift workers, including the security unit (security guard). This study aims to determine the correlation between polymorphonuclear leukocyte levels and gingivitis in the Universitas Muhammadiyah Surakarta (UMS) security unit. This study uses an observational type of analysis with a cross-sectional approach. The sampling technique uses non-probability sampling in the form of purposive sampling. The sample used was 30 UMS security guards. The data were analyzed using the Chi-Square non-parametric statistical test. The data of this study was obtained from the results of an examination of polymorphonuclear leukocyte levels and gingivitis examination in the form of a gingival index of respondents conducted at RSGM Soelastri Surakarta. The instruments used are diagnostic sets and hematology analyzers. The results of this analysis test obtained a significant value with a value of p=0.035. Conclusion of this study There is a relationship between